На шляху до архітектурної освіти і професії майбутнього. кафедрі дизайну архітектурного середовища 15 років – замість звіту - Проскуряков, В. І.; Proskuryakov, V. I. (Видавництво Львівської політехніки, 2018)
Висвітлено феномен кафедри дизайну архітектурного середовища Інституту архітектури Національного університету “Львівська політехніка” у її концептуальному, творчому і часовому розвитку на шляху до архітектурної освіти і професії майбутнього.

The article presents the department of architectural environment design phenomenon at Architecture institute of Lviv Polytechnic National University in its conceptual, artistic and time development towards architectural education and profession of the future. The article highlights the department of architectural environment design phenomenon at Architecture institute in its conceptual, artistic and time development towards architectural education and profession of the future. The main question in current architecture in Ukraine is whether modern architects will be able to continue performing the function of architecture form creators in the future and if yes, then in what way. It means that us – those responsible for architects of the future, those who are aware of teachings of “pioneers”, “great masters”, “designers”, “generators of socialist realism ideas” – have been required to take moral responsibility for all Ukrainian environment and architectural one in particular what takes a lot of courage. It would be worth setting such rules of architectural education thanks to which it would be possible to define conceptual basics of the very profession. Based on this, for 15 years the department leadership has been creating special techniques for teaching and educating architects – designers exclusively. Since the beginning personified studying as well as assisting each student in finding their individual way and goal in the profession have been the educational doctrine of the department. We have also started from teaching future designers to communicate professionally so they could illustrate their opinion with the help of sketches, not verbally in order future clients understood them correctly and unambiguously and did not misinterpret. The tasks of department teachers are to find the goal whilst the tasks of the students are to find solutions and the more mistakes they make during studies the better, since then less of them will be made in a future professional life. However, there are tasks which the department will not be able to solve without answering the following questions. Is the profession of an architect dead-end? Does modern national architecture exist? How much and what should be in architecture which would allow to call it at least the beginning of the national one? Is there modern architecture of “West” and “East”, “North”, “South”? And if yes, where is the boundary between them?
On the way towards architectural education and profession of the future 15 years’ anniversary of the department of architectural environment design – in place of the report
Keywords: феномен; діяльність; концептуальний; творчий часовий розвиток; архітектурна освіта і професія майбутнього; phenomenon; activity; conceptual; artistic time development; architectural education and profession of the future; 72.009.378